Who do you love : a novel - Weiner, Jennifer (Atria Books, 2015)
"A sweeping, modern day fairy tale about first romance and lasting love. When the love you love is the one who got away... Rachel Blum and Andy Landis are just eight years old when they meet late one night in an ER waiting room. Born with a congenital heart defect, Rachel is a veteran of hospitals, and she's intrigued by the boy who shows up all alone with a broken arm. He tells her his name. She tells him a story. After Andy's taken back to a doctor and Rachel's sent back to her bed, they think they'll never see each other again. Rachel grows up wanting for nothing in a fancy Florida suburb, the popular and protected daughter of two doting parents. Andy grows up poor in Philadelphia with a single mom and a rare talent that will let him become one of the best runners of his generation. Over the next three decades, their paths cross in magical and ordinary ways. They make grand plans and dream big dreams as they grow together and apart in starts and stops. Through it all, Andy and Rachel never stop thinking about that night in the hospital waiting room all of those years ago, a chance encounter that changed the course of both of their lives. In this captivating, often witty tale about the bonds between women and men, love and fate, and the truth about happy endings, Jennifer Weiner delivers two of her most memorable characters and a love story you'll never forget"--